Pengaruh Influencer dan Brand Trust Terhadap Keputusan Pembelian Skincare Maydooza pada Mahasiswa Universitas Mataram - Rengganis Ratu Ninggrat; Rusminah HS (Faculty of Economics and Business University of Mataram, 2026)
This study aims to determine the influence of influencers and brand trust on Maydooza skincare purchasing decisions among students of the Faculty of Economics and Business, University of Mataram. The data collection method used a sample survey method with a sample of 100 respondents. The analysis method used multiple linear regression analysis using the Statistical Package for the Social Sciences (SPSS). The results of this study indicate that influencers have a positive and significant influence on purchasing decisions with a calculated t-value for Influencers of 3.204 > 2.262 and Brand Trust has a positive and significant influence on Purchasing Decisions with a calculated t-value of 8.136 > 2.626. The results of this study can be used as a basis for improving purchasing decisions by developing the quality of influencers and brand trust.